2018
DOI: 10.22382/wfs-2018-033
|View full text |Cite
|
Sign up to set email alerts
|

Sorption and Surface Energy Properties of Thermally Modified Spruce Wood Components

Abstract: The objective of this work is to study the water vapor sorption and surface energy properties of thermally modified wood (TMW) components, ie wood processing residuals in the form of sawdust. The thermal modification was performed on spruce wood components using a steam-pressurized laboratoryscale reactor at two different temperature (T ) and relative humidity (RH) conditions, T ¼ 150°C and RH ¼ 100% (TMW150), and T ¼ 180°C and RH ¼ 46% (TMW180). A dynamic vapor sorption (DVS) technique was used to determine w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 56 publications
1
6
1
Order By: Relevance
“…Sorption tests performed at higher temperature conditions will lead to a lower EMC at a given RH. However, it can be concluded that the EMC at 75% RH for the sorption isotherm is in accordance with the moisture content that was obtained from the IGC measurements on the same samples, at 30°C, 75% RH for both TM and UM wood (Källbom et al 2015).…”
Section: C1ssupporting
confidence: 84%
See 3 more Smart Citations
“…Sorption tests performed at higher temperature conditions will lead to a lower EMC at a given RH. However, it can be concluded that the EMC at 75% RH for the sorption isotherm is in accordance with the moisture content that was obtained from the IGC measurements on the same samples, at 30°C, 75% RH for both TM and UM wood (Källbom et al 2015).…”
Section: C1ssupporting
confidence: 84%
“…It is also evident that the wettability, surface chemical composition and surface energetics of TM wood is significantly different compared with conventional wood as well as other types of modification approaches, e.g. acetylation and furfurylation of wood Källbom et al 2015). In a parallel study to this work, Källbom et al (2015) used inverse gas chromatography (IGC) to study the surface energetics of ground TM spruce components indicating significantly higher dispersive surface energy heterogeneity of the modified samples compared with UM samples.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…Little is known about the hygroscopic properties of wood dust from thermally modified wood. Källbom et al (2018) is the only study we are aware of that analyzed hygroscopicity of sawdust, in that case for heat-treated Norway spruce wood, with sorption isotherms evaluated over three adsorption-desorption cycles. They reported that equilibrium moisture content reduction is partially reversible.…”
Section: Introductionmentioning
confidence: 99%